A Brief History of Prohibition and Treatment Solutions for Substance Abusers - Duncan, David F.; Nicholson, Thomas; White, John B.; Ellis-Griffith, Gregory (International Journal of Criminology and Sociology, 2014)
The predominant policy of prohibition (i.e. “War on Drugs”) emerged in the early Twentieth Century. It has been expanded on since that time to become the primary thrust of drug policy in almost every nation today. We will examine how this came about and the ways in which it has contributed to the maltreatment of substance abuse disorders.